PERILAKU AFIRMATIF ORGANISASI SEKOLAH MELALUI MANAJEMEN STRES - Sureni; Kurniawan (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2024)
The phenomenon of stress in life cannot be avoided, including in the scope of the school organization. Stress can give positive and negative impacts in the organizational cycle caused by individuals. The positive impact (eustress) creates a constructive and healthy effect, while the negative impact (distress) causes destructive effect, one of the behaviors that emerges is stress. Therefore management is needed in dealing with stress that occurs within the scope of the school organization. Appropriate stress management can motivate individuals and provide positive stigma, thereby giving to positive affirmative behavior. Positive behavior in school organizations; structure, culture, processes, leadership and other organizational conditions. The goal of writing this article is to describe stress management as an effort to create positive affirmative behavior in school organizations. The research method utilize library research. The outcome of the study explained that stress management can create positive affirmative behavior within the scope of the school organization, as well as supporting material for achieving school organizational goals, so that efforts to build positive behavior can create a conducive climate in realizing organizational goals.